Effects of PZT content and particle size on ferroelectric hysteresis behavior of 0-3 lead zirconate titanate - Portland cement composites - N. Jaitanong (2018)
Lead Zirconate Titanate (PZT)-cement composites of 0-3 connectivity were produced and the effects of PZT particle size and PZT content on the ferroelectric hysteresis behavior were investigated. It is clear from the hysteresis measurements that the particle size has a strong influence on the polarization-electric field loop of composites with smaller particle sizes of 75 μm and 212 μm the loops were found to exhibit a lossy characteristic. At 425 μm particle size, the composite exhibits a more typical ferroelectric hysteresis loop. There is also a significant increase in the remnant polarization with increasing particle size where the composite of 425 μm was found to have a significantly higher instantaneous remnant polarization (Pir) in comparison to the composites with smaller particle sizes. Furthermore, Pirwas found to increase as PZT volume increases from 40-60%, while coercive field (Eic) decreased and reached a saturated value when PZT volume content is 60%. Copyright © Taylor & Francis Group, LLC.